Heterogennost a homogennost ve stylové sfére - MARIE (Stylistyka, 2021)
The author discusses the manifestations of the principles of heterogenity and homogenity in various stylistis spheres. Both of these principles - as a competing opposition or as a continuum - influence the creation of text style and its reception.